Cover Picture: Observation of the FeCN and FeCO Vibrations in the Active Site of [NiFe] Hydrogenase by Nuclear Resonance Vibrational Spectroscopy (Angew. Chem. Int. Ed. 2/2013). Issue 2 (26th November 2012) - Kamali, Saeed; Wang, Hongxin; Mitra, Devrani; Ogata, Hideaki; Lubitz, Wolfgang; Manor, Brian C.; Rauchfuss, Thomas B.; Byrne, Deborah; Bonnefoy, Violaine; Jenney, Francis E.; Adams, Michael W. W.; Yoda, Yoshitaka; et al.
<x xml:space="preserve">Abstract</x> The active site of [NiFe] hydrogenase is an excellent catalyst for hydrogen conversion with an intriguing ability to recover from exposure to dioxygen. In their Communication on page 724 ff., W. Lubitz, S. P. Cramer, and co‐workers use the synchrotron technique of nuclear resonance vibrational spectroscopy to identify normal modes associated with active‐site FeCN and FeCO motion.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>